Beyond the clinic: The role of the psychiatrist in practicing pragmatic solidarity - Anne Berhe; Abishek Bala; Tobi Okopie; Jennifer Agwagom; Manal Khan; Suzan J. Song (PLOS Mental Health, 2026)
Psychiatrists are trained to evaluate biological, psychological, and social dimensions of illness simultaneously, yet the dominant frameworks governing psychiatric practice remain oriented toward individual symptom management rather than the structural conditions that produce these symptoms. This essay argues that psychiatrists working in global mental health contexts carry an ethical obligation that extends beyond diagnosis and treatment: to practice what Paul Farmer termed pragmatic solidarity, the practice of standing alongside communities to address the upstream drivers of mental distress through structural advocacy, community-led care, and institutional accountability. This essay draws on evidence from three intersecting domains. First, it examines the well-documented global mental health burden, including treatment gaps and the disproportionate impact of conflict, displacement, and structural inequity on psychological wellbeing. Second, it argues that effective global mental health work requires horizontal partnerships, epistemic justice, and the centering of community-defined priorities over externally imposed frameworks. Third, it illustrates what pragmatic solidarity looks like in individual, institutional and policy contexts. Importantly, this essay is a call to action, identifying concrete entry points through which psychiatrists can move from recognition of structural drivers to active participation in dismantling them, including through material redistribution, community partnership, participatory research, and policy engagement. Pragmatic solidarity offers psychiatrists not just a theoretical framework, but a tangible, enactable way of improving global mental health.